Квантові вейвлет перетворення - Гальченко, К. Р. (ХНУРЕ, 2025)
The paper describes the promising directions of using quantum wavelet transforms (QWT) in the field of image processing, as well as the components of these transforms. The use of QWT allows for efficient image compression while preserving detail and more accurate color space information. For example, the quantum wavelet transform can be used to encode images in quantum states with subsequent restoration.
Keywords: квантові вейвлет перетворення; quantum wavelet transforms